The diffusion of mobile phones in India - K. Singh, Sanjay (2007)
Mobile phones, which were introduced a decade ago in 1995-96 in India, are becoming the dominant means of accessing communication. At the end of 2005-06, there were 90 million mobile subscribers in India in comparison to 50 million subscribers for landlines. The increase in mobile phones has been phenomenal in comparison to landlines since the introduction of mobiles in the country. The main aim of this paper is to estimate the future trend and analyze the pattern and rate of adoption of mobile phones in India. The paper uses S-shaped growth curve models for the same. It is found that mobile-density (number of mobile phones per 100 inhabitants) in India will increase from 8.1 in 2005-06 to 36.5 in 2010-11 and 71 in 2015-16. Consequently, mobile subscriber base is projected to increase from 90 million in 2005-06 to 433 million in 2010-11 and nearly 900 million in 2015-16.The projected rapid growth in mobile subscriber base will have important implications for future plans of mobile operators, infrastructure providers, handset suppliers, and vendors. Mobile operators should be ready with contingency plans to deploy and operate infrastructure including customer care, billing, applications, etc., faster than that they might have initially planned. Infrastructure providers, handset suppliers, and vendors should be prepared to respond to such plans.